Strategi Konservasi Kebudayaan Lokal Yogyakarta - Amiluhur Soeroso; Y Sri Susuilo (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
The purpose of this paper is assessing conservation strategy of Yogyakarta local culture to muffle attacking globalization of cultural economic and cultural industry. We do looking for effectual strategy to develop cultural tourism based on creativity sense. We first identify important factors that confound the physic and entity culture using factor and cluster analysis. Following this, we apply expert choice to enact the strategy. We conclude that important factors for the conservation of culture are introducing the Javanese eco-culture to society early on, revitalizing the ritual tradition and conserving the traditional dance and music. In addition, we propose the policy brief in order to become the important reference of cultural tourism development. The important policies are giving cognitive, affective and conative education to people, and reanimating traditional jackstraws.